Memory of voice - Revel, Nicole (Philippine Journal of Linguistics, 2006)
In today's world, an outstanding poetic and musical heritage is present in living memories and practices among many Austronesian languages and cultures. In spite of the many studies conducted since World War II, a great deal remains to be listened to, collected, safeguarded, transcribed, translated, analyzed and comprehended. Modern technologies are now available which can be explored and developed in our respective attempts to do so. This paper focuses on the Nusantara region, the Western branch of the Austronesian family, and more particularly on the Philippines, where, since 1992, we have begun to build up a "Philippine Oral Epics Archive?, based at Ateneo de Manila University. This tridimensional audio, audio-video and computerized archive will be presented briefly. A pluridisciplinary approach is employed in order to capture a "mental text", and its elaboration in performance. Specific aspects considered include: - the role of deixis related to action and text processing, particularly in repetitive segments and in the macrostructure of the plot; - the close relationship between words and music; - the projection of time in space in establishing the first manuscript of a sung poetic composition; - the referential knowledge encapsulated in the narratives and the teachings they convey, will be successively referred to and illustrated. Finally, epic singing is analyzed as a vocal "skilled activity?. Linguistics, Ethnography, Ethnomusicology and Cognitive Linguistics-Anthropology will contribute to our understanding of this creative process.